Tomografía cerebral, SPECT cerebral y neurocognición en trauma craneoencefálico - Casallo Quiliano , Carlos (2013)
Introduction: Computed tomography (CT) is the primary diagnostic tool used in evaluating acute Trauma Brain Injury (TBI). Single-photon Emission Computerized Tomography (SPECT) is been used in TBI, with better results in brain functional evaluation than CT or MRI. Relationship between CT and SPECT after TBI was studied, but neurocognitive status is not included. Patients may have neurocognitive impairment with none or few abnormalities in structural images from CT. Material and Methods: Twenty patients between 16 and 60 years old with mild or moderate trauma brain injury were studied. CT scan, brain SPECT and neuropsychological evaluation were made at admission. Obtained data was matched. Results: CT scan and SPECT were abnormal in 16 and 19 patients. CT scan showed 15 brain lesions and SPECT 29 brain lesions. All patients with neurocognitive impairment had an abnormal SPECT. Discussion: Brain SPECT is more sensitive than CT scan detecting number of cerebral lesions in mild and moderate TBI. Patients with neurocognitive deficit after TBI have an abnormal SPECT.